2007
DOI: 10.1186/1471-2458-7-73
|View full text |Cite
|
Sign up to set email alerts
|

Marital status and mortality among Japanese men and women: the Japan Collaborative Cohort Study

Abstract: Background: Several studies have indicated a significant association between marital status and mortality risks. However, most of these studies have compared married and unmarried people without differentiating among single, divorced and widowed status. Moreover, gender differences in mortality rates associated with marital status have not been sufficiently clarified. With significant increases in the percentages of divorced and widowed people and a corresponding drop in the marriage rate in Japan during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

9
142
3
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(162 citation statements)
references
References 24 publications
9
142
3
8
Order By: Relevance
“…This observation, which was similar to those in endometrial and ovarian cancers, was inconsistent with the results obtained from previous studies (Hirose et al 1996; International Collaboration of Epidemiological Studies of Cervical Cancer 2006). We suppose that the effects of marital status and parity on cervical cancer risk in the present study could be explained not by etiological factors but rather by certain factors related to health behaviors; for example, unmarried or nulliparous women, who may be unconcerned about gynecologic diseases, may rarely visit gynecologic clinics and cancer screening centers (Kato et al 1987;Ikeda et al 2007). Such women may miss the chance of treating dysplasia or carcinoma in situ and are likely to fall victim to more serious disease, i.e., invasive cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This observation, which was similar to those in endometrial and ovarian cancers, was inconsistent with the results obtained from previous studies (Hirose et al 1996; International Collaboration of Epidemiological Studies of Cervical Cancer 2006). We suppose that the effects of marital status and parity on cervical cancer risk in the present study could be explained not by etiological factors but rather by certain factors related to health behaviors; for example, unmarried or nulliparous women, who may be unconcerned about gynecologic diseases, may rarely visit gynecologic clinics and cancer screening centers (Kato et al 1987;Ikeda et al 2007). Such women may miss the chance of treating dysplasia or carcinoma in situ and are likely to fall victim to more serious disease, i.e., invasive cancer.…”
Section: Discussionmentioning
confidence: 99%
“…ПРОФИЛАКТИЧЕСКАЯ МЕДИЦИНА, 1,2016 эффект от ФССР, развития сердечно-сосудистых заболе-ваний и смертности [9,10]. Результаты настоящего иссле-дования не укладываются в данную концепцию благопри-ятного влияния наличия семьи на распространенность ФССР.…”
Section: Discussionunclassified
“…Not being married was associated with the healthy intake of most nutrients including vitamins and fiber, particularly for women. Prior studies in Japan found that being married decreased mortality and morbidity (21,22), so married people are assumed to have a healthier diet than unmarried people. Several studies in other countries found that married individuals tend to eat healthier diets than unmarried individuals do (23)(24)(25)(26), while a few studies had inconsistent findings (27,28).…”
Section: Discussionmentioning
confidence: 99%